Generalised joint hypermobility as a symptom of chosen diseases and syndromes - Przymuszała, Aneta; Roszak, Magdalena; Kulik, Oksana; Uździcki, Artur; Turon-Skrzypinska, Agnieszka; Rotter, Iwona; Ptak, Magdalena (Journal of Education, Health and Sport, 2018)
Hypermobility is defined as ability to actively or passively perform a move, which exceed the norm for range of movement for each joint. In any case of hypermobility it is crucial to determine if it is a sign of pathological process. Join hypermobility is a frequent abnormality in a general population and may be caused by a numerous genetic disorders. The aim of this paper is to compare the most important diseases which may manifest in generalized joint hypermobility. This study include available knowledge about hypermobility in particular diseases and syndromes which are: Joint Hypermobility Syndrome, Ehlers-Danlos Syndrome Hypermobility Type, Marfan Syndrome, Loeys - Dietz Syndrome, Down Syndrome, Fragile X Sydrome.